SEHATI: PELUANG DAN TANTANGAN PEMBERIAN SERTIFIKASI HALAL GRATIS BAGI PELAKU UMK DI INDONESIA - Ahmad Havid Jakiyudin; Alfarid Fedro (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2022)
The government has ambitions to make Indonesia to be a center for halal producers by 2024. Sehati Program (free halal certification) was launched for all MSEs in Indonesia. However, relevant in-depth to find out whether this program can realize Indonesian dreams. The purpose of this research is to analyze the opportunities and challenges of the implementation of Sehati Program. A qualitative descriptive research method with a normative juridical type is used to answer the research results. Various laws and regulations related to the guarantee of halal products are collected and used as the main analysis material. The results of the study indicate that the one heart program is not intended for all MSEs in Indonesia. This program relies on the self-declared provisions as stipulated in PP No. 33 of 2021 concerning the Implementation of a Halal Product Guarantee and PMA No. 20 of 2021 concerning Halal Certification for Micro and Small Business Actors. The healthy program has the opportunity to make Indonesian products competitive advantages. The large amount of budget needed by the government and the emergence of doubts about the halalness of the product are challenges.Keyword: Sehati, Halal Product, MSEs